Effect of High‐Temperature Calcination on the Generation of Brønsted Acid Sites on WO3/Al2O3. Issue 7 (6th June 2014) - Kitano, Tomoyuki; Hayashi, Tomohiro; Uesaka, Toshio; Shishido, Tetsuya; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract The acid properties of a series of alumina‐supported tungsten oxide (WO3/Al2O3) catalysts with loadings of 5–50 wt % WO3 calcined at various temperatures were investigated by acid‐catalyzed reactions (benzylation of anisole and isomerization of α‐pinene) and FTIR spectroscopy. The relationships between acid properties, structures, and catalytic performances were evaluated. Both the catalytic activity and amount of Brønsted acid sites depend on the calcination temperature and WO3 loading. High‐temperature calcination (1123 K) generated Brønsted acid properties, and 20 wt % WO3/Al2O3 calcined at 1123 K exhibited the highest activity among the catalysts tested. The activities for the benzylation of anisole and α‐pinene isomerization over WO3/Al2O3 calcined at 1123 K were proportional to the Brønsted acidity, which indicates that these reactions occurred on the Brønsted acid sites. Tungsten oxide, which has distorted octahedral symmetry, was loaded as 2 D monolayer domains below 20 wt %, and these domains covered most of the alumina surface at 20 wt %. If the WO3 loading was sufficient to form 2 D tungsten oxide monolayer sheets (>20 wt %), some of the Brønsted acid sites on WO3/Al2O3 were obscured by monoclinic WO3 that has no Brønsted acid sites, which resulted in a decrease of the catalytic activity. This suggests that Brønsted acid sites are generated at the boundaries between tungsten oxide monolayer domains.